Amalan konsep wakalah pengurusan zakat di Politeknik Ungku Omar - Ammar Badruddin, Romli (Center for Communication Technology and Human Development (UniMAP), 2022)
Link to publisher's homepage at https://johdec.unimap.edu.my/